Modern Conservative Judaism : evolving thought and practice - Dorff, Elliot N. (Lincoln : University of Nebraska Press, 2018)
"A Conservative Movement insider's guide to the evolution of Conservative Jewish thought and practice over the last half century, offering insight into the diverse (and occasionally contentious) thought processes behind the movement's most important laws, policies, and documents"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Conservative Judaism -- History -- 20th century; Conservative Judaism; RELIGION / Judaism / General; 1900-1999; History; Electronic books